Analysis of Retaining Wall Calculations in the Pollux Meisterstadt Habibie Batam Project with Indian Standard - Jody Martin Ginting; Vivianty Vivianty (Litbang Pemas - Universitas Islam Lamongan, 2022)
Soil retaining wall infrastructure is an important supporting structure in preventing soil cladding. This infrastructure has as much in the city as a basement development. The design of the infrastructure requires effective and efficient standardization and with the difference in standardization of other countries, it does not hurt to try to use foreign standards to find out the difference. This research aims to analyze the moment of upsizing, shearing force with Indian Standard where data obtained from the field. The methods that have been used for this analysis are observational studies, literatures and interviews with consultants. In this research, the author produced calculations by the author regarding the reinforcements used in the field with SNI and the results of comparisons calculated by the author with the Indian Standard. This analyst started from calculating the moment of scrolling, the sliding force that will occur on the retaining wall then from the moment and we got the required reinforcement on the retaining wall. With existing loads and factors used according to Indian standards, especially in IS 456-2000. The resulting report on the results of comparison and the cause of the need for reinforcements realized with those that have been taken into account.